(untitled) (Doctor Virtualis, 2025)
The Middle Ages that are narrated live a contradictory history: in it we forget that in its context universities are born, where a dialogical dimension prevails. To seek a brief genealogy of the prejudices that cross the theoretical dimension of the Middle Ages is the aim of this work. The conclusion is that, in its various directions and interpretations, a rereading of the Middle Ages must take into account the multiplicity of texts that a tradition is made of: and these texts are not tiles that are placed at will on an imaginary chessboard, which reflects not the whole of history, but only the contingent readings of its contingent author, but must look at the clues that are revealed in these texts, and that direct the interpretation itself. Only through the identification of such clues can we arrive at a redefinition of the interpretative paths.